Effect of Rearing Density of ”Dumbo” Catfish (Clarias sp.) Fry on Production in the Controlled Nitrogen Culture System by Adding Wheat Powder - Shafruddin, D.; Yuniarti, .; Setiawati, Mia (Jurnal Akuakultur Indonesia, 2006)
Demand of "dumbo" catfish is going to increase every year so that fry production should be increased in order  to support intensification culture system to meet market demand. Intensification in fish culture system may cause decreasing of dissolved oxygen content  and producing high level waste in the pond culture.  The effort to control inorganic nitrogen in intensive culture system can be performed by adding wheat powder into fish culture media.  This can support metabolic process of nitrogen by microbe and then produce protein in terms of bacteria biomass production, so that inorganic nitrogen in the water decreases.  Fish can utilize protein from  microbe efficiently. This study was conducted to examine effect of rearing density on "dumbo" catfish fry production in the culture system by controlling nitrogen content in water through addition of  wheat powder.  "Dumbo" catfish fry of 12-day old in average body weight of 0.046±0.006 gram and length of 1.7±0.9 cm were reared for 28 days in density of 400, 800 and 1200 fish/m2.  The results of study showed that weight and body length of fry reached 1.35 gram and 5.1 cm, respectively. Average of daily growth and production were 10.47 - 11.48% and 2.49 - 3.54 g per day, respectively. Increased of rearing density was insignificantly (p>0.05) affected growth rate and daily production.  Average growth in absolute length, survival rate and feed efficiency was about 2.7-3.2 cm, 36.20 - 53.88% and 147 - 172%, respectively.  Increased in rearing density was followed by decreased growth in length (p0,05) terhadap laju pertumbuhan dan produksi harian. Nilai rata-rata pertumbuhan panjang mutlak, kelangsungan hidup dan efisiensi pakan masing-masing berkisar 2,7-3,2 cm, 36,20 - 53,88% dan 147 - 172%. Peningkatan kepadatan diikuti dengan penurunan pertumbuhan panjang (p